2018
DOI: 10.1016/j.jpsychires.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in mental health service utilization in suicidal adults: A nationally representative study

Abstract: The current study examined racial/ethnic differences in utilization of mental health services in a nationally representative sample of suicidal adults. Data were extracted from the National Survey on Drug Use and Health (NSDUH) from 2009 to 2016. Participants consisted of adults with severe suicidal ideation and/or behavior in the past 12 months (unweighted n = 17,338). Multivariate logistic regression analyses were conducted to assess racial/ethnic differences in mental health treatment utilization after adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Despite the previously argued reluctance by many Indigenous Australians to engage with Western-based medical models of treatment [ 48 ], their rates of suicidal presentations to our EDs remained much higher than those of non-Indigenous persons. It is possible that among presentations by Indigenous persons included in our analysis, a greater proportion resulted from suicide attempts, particularly if using methods that are more likely to require medical interventions [ 14 ] or were involuntary in nature [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the previously argued reluctance by many Indigenous Australians to engage with Western-based medical models of treatment [ 48 ], their rates of suicidal presentations to our EDs remained much higher than those of non-Indigenous persons. It is possible that among presentations by Indigenous persons included in our analysis, a greater proportion resulted from suicide attempts, particularly if using methods that are more likely to require medical interventions [ 14 ] or were involuntary in nature [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presentations with suicidal ideation have a higher rate of re-presentations than suicide attempts [ 11 ] and are more frequent among males than females [ 11 , 12 ]. Racial and ethnic differences have also been found to impact on rates of suicidal presentations to EDs, with evidence of members of ethnic minority groups displaying a higher risk of suicide yet being less likely to engage with mental health services [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, black participants had a 4.2 higher adjusted SGRQ score for a hospitalized exacerbation compared to white participants [21]. Black participants may also experience racial discrimination as well as have differences in health behaviors including delays in seeking mental health treatment that may affect quality of life [22,23]. Exacerbation status is reflective of only two points in time; therefore we also performed multivariable logistic regression models for QoL decline with yearly exacerbation frequency as the predictor of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that across all older adults in need of mental health treatment, Black participants are less likely to receive culturally effective care (Jimenez et al 2012). Similarly, among persons experiencing a mental health crisis, service utilization was lowest among non-Hispanic Blacks, Hispanics, and multiracial individuals (Sheehan et al 2018). The following section describes the actual impact of Medicare Parts B and D on African American and Latin/x older adults with a specific focus on the challenges of this policy and subsequent programming.…”
Section: Phase Five: Actual Impactmentioning
confidence: 99%